ABC drug transporters and immunity: novel therapeutic targets in autoimmunity and cancer - Ven, Rieneke; Oerlemans, Ruud; Heijden, Joost W.; Scheffer, George L.; Gruijl, Tanja D.; Jansen, Gerrit; Scheper, Rik J. (Journal of leukocyte biology, 2009)
Review evaluates the possible physiological roles of MDR‐related ABC transporters on immune effector cells based on reports on their expression patterns and immune‐related substrates. ABC transporters were identified originally for their contribution to clinical MDR as a result of their capacity to extrude various unrelated cytotoxic drugs. More recent reports have shown that ABC transporters can play important roles in the development, differentiation, and maturation of immune cells and are involved in migration of immune effector cells to sites of inflammation. Many of the currently identified, endogenous ABC transporter substrates have immunostimulating effects. Increasing the expression of ABC transporters on immune cells and thereby enhancing immune cell development or functionality may be beneficial to immunotherapy in the field of oncology. On the contrary, in the treatment of autoimmune diseases, blockade of these transporters may prove beneficial, as it could dampen disease activity by compromising immune effector cell functions. This review will focus on the expression, regulation, and substrate specificity of ABC transporters in relation to functional activities of immune effector cells and discusses implications for the treatment of cancer on the one hand and autoimmune diseases on the other.